Determinants of tPA Antigen and Associations with Coronary Artery Disease and Acute Cerebrovascular Disease - Carter, Angela M.; Catto, Andrew J.; Grant, Peter J. (Thrombosis and Haemostasis, 1998)
The aim of this study was to determine the association of tPA antigen levels with CAD and ischaemic stroke and whether associations are independent of levels of PAI-1 antigen. In subjects with CAD (n = 247) tPA was associated with the number of coronary arteries with ≥50% stenosis, but this association was lost after adjustment for PAI-1, which was found to be the largest determinant of tPA levels in linear regression models and accounted for as much as 38% of the variation in levels. Levels of tPA were significantly higher in patients with a history of MI compared with those without, even after adjustment for covariates and PAI-1 (MI: 10.0 [9.4-10.6] ng/ml; no MI: 8.9 [8.5-9.4] ng/ml, p = 0.004). In a logistic regression model comparing patients with MI to patients without MI, the odds ratio for tPA levels in the upper quartile compared with the lowest quartile was 2.03 (1.33-3.10). Levels of tPA in subjects with ischaemic stroke (n = 338) were significantly higher than age matched healthy control subjects (n = 366) and again this difference remained after adjustment (patients: 10.4 [9.9-10.9] ng/ml; controls: 9.0 [8.7-9.3] ng/ml, p <0.0001). In a logistic regression model comparing patients with ischaemic stroke to healthy control subjects the odds ratio for tPA in the upper quartile compared with the lowest quartile was 4.23 (3.02-5.92). These data suggest that the associations of tPA with acute thrombosis are independent of levels of PAI-1 but the mechanisms whereby enhanced fibrinolysis may predis-pose to thrombosis remain unclear.